2015
DOI: 10.1128/aac.00494-15
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin B in Combination with Antimicrobials Lacking In Vitro Activity versus Polymyxin B in Monotherapy in Critically Ill Patients with Acinetobacter baumannii or Pseudomonas aeruginosa Infections

Abstract: There is no clinical evidence supporting the use of polymyxin B in combination with another antimicrobial for infections caused by extensively drug-resistant Acinetobacter baumannii or Pseudomonas aeruginosa isolates. We developed a cohort study of patients in two intensive care units from teaching hospitals to evaluate treatment with intravenous polymyxin B for >48 h for severe A. baumannii or P. aeruginosa infections. Covariates potentially associated with 30-day mortality were evaluated in a Cox proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 23 publications
1
45
0
7
Order By: Relevance
“…The related cationic peptide antibiotics colistin and polymyxin B are increasingly being used as last-line agents for treatment of patients with highly multidrug-resistant strains of P. aeruginosa [43, 44]. Since these agents have similar charge characteristics and mechanisms of action to the host defense peptide LL-37, we examined the effect of the vacJ inactivation on sensitivity to these therapeutic agents.…”
Section: Resultsmentioning
confidence: 99%
“…The related cationic peptide antibiotics colistin and polymyxin B are increasingly being used as last-line agents for treatment of patients with highly multidrug-resistant strains of P. aeruginosa [43, 44]. Since these agents have similar charge characteristics and mechanisms of action to the host defense peptide LL-37, we examined the effect of the vacJ inactivation on sensitivity to these therapeutic agents.…”
Section: Resultsmentioning
confidence: 99%
“…Although the standard antimicrobial scheme against A. baumannii infections has not been fully established, evidence supports the fact that combination therapies including polymyxin B are more effective than polymyxin B monotherapies. Moreover, polymyxin B combined with a second antimicrobial agent was able to reduce hospital mortality rates, and has been widely recommended due to resistance emerging in some A. baumannii strains during treatments [2][3][4]. Nevertheless, antimicrobial therapy failure has been reported, especially in recalcitrance of chronic infections, which may be due to the tolerance mediated by persister cells [5,6] -a microbial subpopulation able to survive to normally lethal concentrations of bactericidal antimicrobials [7], as has been previously described in Acinetobacter spp.…”
Section: Combination Of Polymyxin B and Meropenem Eradicates Persistementioning
confidence: 99%
“…Like previous nonrandomized studies, we observed large variability in the baseline and treatment characteristics between the treatment groups in our study (35,36). It is noteworthy that patients in the VCT group had significantly more comorbidities, higher APACHE II scores, and higher incidences of secondary bacteremia (bacteremia complicating a primary infection site).…”
Section: Discussionmentioning
confidence: 45%